Tarifa social e subsídio cruzado: o mito da universalidade do transporte público brasileiro - Barouche, Tônia de Oliveira [UNESP] (2015)
The public policy of the social tariff, combined with the cross-subsidy is undoubtedly one of the most important topics covered in the news when speaking in the universal realization of the right of public transport to the poor, as it consists in an alternative used by the Government to assist and/or benefit specific group of underprivileged users through discriminatory low-income factor, through the emanation of municipal laws granting tariff benefits to classes of economically disadvantaged users, transferring the cost of operation to the other users. However, recent studies show that the poor still suffer from social exclusion and inability to pay the price of fares. Thus, this study aims to investigate the real effectiveness of the combined social tariff policy with cross-subsidy in the Brazilian municipal public transport when analyzing your main scope: universal public service in terms of the scope of the principle of substantive equality. Therefore, the methodology used is basically inductive-deductive combined with empirical research